Answer:
x = -5 y = -3
Step-by-step explanation:
-3x + 2y = 9
multiply the 2nd equation by 3 to set it up for elimination
3(x - 3y)= 3(4)
3x-9y = 12
so now combine both to add
-3x + 2y = 9
3x - 9y = 12
Adding both gives you
-7y = 21
divide both by -7 and you get
y = -3
and you substitute y back into equation to get x
x - 3 (-3) = 4 gives you
x + 9 = 4
x = 4 - 9
x = -5
Answer:
Not sure, It's getting kinda annoying ngl
Step-by-step explanation:
Answer:
y=5200(0.85)^x
Step-by-step explanation:
A photocopier is purchased for $5200 and depreciates in value by 15% per year. Which equation best describes the value of the photocopier in years? O.A. y=5200(1.15) OB. y = 5200(0_15) - O cy= 5200(1.85) ODy=5200(0.85)"
It’s a
100-25= 75
75 divided by 0.01
0.75 x 18